Anode active material, anode including the same, secondary battery including the same, and method for producing anode active material

The development of a SiOx-based negative electrode active material with specific BET surface area and powder conductivity addresses the inefficiencies and lifespan issues in lithium secondary batteries, resulting in improved initial efficiency and extended battery life.

JP7657940B2Active Publication Date: 2025-04-07LG ENERGY SOLUTION LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023543030
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-13
Filing Date
2022-08-11
Publication Date
2025-04-07
Estimated Expiration
2042-08-11

AI Technical Summary

Technical Problem

Existing lithium secondary batteries using silicon-based negative electrode active materials face issues such as reduced initial efficiency due to irreversible phase formation and excessive volume change during charging and discharging, leading to shortened battery life.

Method used

A negative electrode active material is developed, comprising SiOx (0

Benefits of technology

The optimized negative electrode active material enhances the initial efficiency and extends the lifetime of lithium secondary batteries by reducing side reactions and volume changes during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657940000001
    Figure 0007657940000001
  • Figure 0007657940000002
    Figure 0007657940000002
Patent Text Reader

Abstract

The present invention relates to a silicon-based composite particle containing SiO x (0 < x < 2) and a Mg compound or a Li compound; and a negative electrode active material including a carbon layer provided on the silicon-based composite particle, wherein the BET specific surface area of the silicon-based composite particle is 5 m 2 / g to 60 m 2 / g, the BET specific surface area of the negative electrode active material is 2 m 2 / g to 15 m 2 / g, and the powder conductivity at a powder density of 1.4 g / cc is 0.05 S / cm to 1 S / cm. The present invention also relates to a negative electrode including the negative electrode active material, a secondary battery including the negative electrode, and a method for manufacturing the negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2021-0107517, filed with the Korean Intellectual Property Office on August 13, 2021, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a negative electrode active material, a negative electrode including the same, a secondary battery including the same, and a method for producing the negative electrode active material. [Background technology]

[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and as part of this, the field in which research is most active is the field of power generation and storage using electrochemical reactions.

[0004] At present, a representative example of such electrochemical elements that use electrochemical energy is a secondary battery, and the range of its use is expanding. In recent years, with the increase in technological development and demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as energy sources has increased rapidly. Among the secondary batteries, many studies have been conducted on high energy density, i.e., high capacity lithium secondary batteries, which have been commercialized and are widely used.

[0005] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material that inserts and removes lithium ions that have come out of the positive electrode. Silicon-based particles with a large discharge capacity can be used as the negative electrode active material. However, SiO x The SiO2 in the silicon-based particles (0≦x<2) reacts partially with the lithium ions transferred from the positive electrode to generate lithium silicate, which acts as an irreversible phase and reduces the initial efficiency of the battery. In addition, the silicon-based particles change volume excessively during charging and discharging, causing side reactions with the electrolyte. This causes a problem of reduced battery life.

[0006] In the past, in order to solve these problems, a technology has been used in which metals such as Mg are intentionally doped into silicon-based particles to block reaction sites that may form in irreversible phases and improve initial efficiency. However, even if the initial efficiency can be improved, simply doping a metal without considering the appropriate composition makes it difficult to improve the battery's life characteristics, and there is a problem that metal doping causes a significant decrease in capacity per weight.

[0007] Meanwhile, when metal-doped silicon-based particles are prepared, the particles are easily oxidized, which causes a problem of a decrease in initial efficiency of the battery. Therefore, a method for preventing such a decrease in initial efficiency of the battery is required.

[0008] In addition, in order to improve the conductivity of the negative active material, a carbon coating layer may be formed on the metal-doped silicon-based particles to manufacture the negative active material. However, simply forming a carbon coating layer has a limited effect on improving the conductivity, and therefore, has a limited effect on improving the life characteristics of the battery. Thus, a method for further improving the conductivity of the negative active material is required. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Korean Patent Publication No. 10-2019-0101767 Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a negative electrode active material capable of improving the initial efficiency and life characteristics of a battery.

[0011] Another object of the present invention is to provide a negative electrode including the negative electrode active material.

[0012] Another problem that the present invention aims to solve is to provide a secondary battery including the negative electrode.

[0013] Still another problem that the present invention aims to solve is to provide a method for manufacturing the negative electrode active material.

Means for Solving the Problems

[0014] One embodiment of the present specification is silicon oxide x (0 < x < 2) and silicon-based composite particles containing a Mg compound or a Li compound; and a negative electrode active material including a carbon layer provided on the silicon-based composite particles, wherein the BET specific surface area of the silicon-based composite particles is 5 m 2 / g to 60 m 2 / g, the BET specific surface area of the negative electrode active material is 2 m 2 / g to 15 m 2 / g, and the powder conductivity at a powder density of 1.4 g / cc is 0.05 S / cm to 1 S / cm, to provide a negative electrode active material.

[0015] One embodiment of the present specification is a step of manufacturing silicon-based composite particles containing silicon oxide x (0 < x < 2) and a Mg compound or a Li compound; and a step of providing a carbon layer on the surface of the silicon-based composite particles, to provide a method for manufacturing the negative electrode active material.

[0016] One embodiment of the present specification provides a negative electrode including the negative electrode active material.

[0017] One embodiment of the present specification provides a secondary battery including the negative electrode.

Effects of the Invention

[0018] The negative electrode active material according to one embodiment of the present specification includes silicon-based composite particles having a low level of BET specific surface area. Since the negative electrode active material has a low level of BET specific surface area and high powder conductivity, the initial efficiency and life characteristics of the battery can be improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] In the following, the present invention will be described in more detail to facilitate understanding of the present invention.

[0020] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0021] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. The singular expressions include the plural expressions unless otherwise clearly indicated in the context.

[0022] It should be understood that, as used herein, terms such as "comprises," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0023] In this specification, the pore size may refer to the average diameter of the pores contained in the negative electrode active material, that is, the size may indicate the average diameter of the pores.

[0024] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50) can be measured, for example, using the laser diffraction method. The laser diffraction method can generally measure particle sizes in the submicron region to about several millimeters, and can obtain highly reproducible and highly resolved results.

[0025] In this specification, the specific surface area can be measured for the measurement object using a BET measuring device (BEL-SORP-MAX, Nippon Bell), removing gas (degassing) at 200 °C for 8 hours, and performing N2 adsorption / desorption at 77K and measuring by the BET six-point method.

[0026] In this specification, the powder conductivity can be measured using an HPRM-1000 device manufactured by HAN TECH. Specifically, after positioning an empty holder (diameter 10 mm) in the 4-probe, the initial thickness when the initial pressure is 10 kgf is measured. After confirming the initial thickness of the holder, approximately 3 g of the active material is placed in the holder (diameter 10 mm), the holder is positioned in the 4-probe, and then sample information is input. Pressure is applied to the holder containing the sample, and the powder conductivity can be measured based on the powder density at that pressure.

[0027] <Negative electrode active material> The negative electrode active material according to one embodiment of this specification is SiO x (0 < x < 2) and silicon-based composite particles containing a Mg compound or a Li compound; and a negative electrode active material including a carbon layer provided on the silicon-based composite particles, wherein the BET specific surface area of the silicon-based composite particles is 5 m 2 / g to 60 m 2 / g, the BET specific surface area of the negative electrode active material is 2 m 2 / g to 15 m 2 / g, and the powder conductivity at a powder density of 1.4 g / cc may be 0.05 S / cm to 1 S / cm.

[0028] The negative electrode active material according to an embodiment of the present specification includes silicon-based composite particles. The silicon-based composite particles include SiO x (0 < x < 2) and a Mg compound or a Li compound.

[0029] The SiO x (0 < x < 2) may correspond to a matrix within the silicon-based composite particles. The SiO x (0 < x < 2) may be in a form containing Si and SiO2, and the Si may form a phase. That is, the x corresponds to the number ratio of O to Si contained in the SiO x (0 < x < 2). When the silicon-based composite particles contain the SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0030] The silicon-based composite particles may include SiO x (0 < x < 2) and a Mg compound.

[0031] The silicon-based composite particles may include SiO x (0 < x < 2) and a Li compound.

[0032] In one embodiment of the present specification, the Mg compound or the Li compound may be present inside and / or on the surface of the SiO x (0 < x < 2). The initial efficiency of the battery can be improved by the Mg compound or the Li compound. The Mg compound or the Li compound may correspond to a matrix within the silicon-based composite particles.

[0033] The Mg compound may include at least any one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The Mg silicate may include at least any one of Mg2SiO4 and MgSiO3. The Mg silicide may include Mg2Si. The Mg oxide may include MgO.

[0034] The Li compound may include at least one selected from the group consisting of Li silicate, Li silicide, and Li oxide. The Li silicate may include at least one of Li2SiO3, Li4SiO4, and Li2Si2O5. The Li silicide may include Li7Si2. The Li oxide may include Li2O.

[0035] In one embodiment of the present specification, the Mg element or Li element may be contained in an amount of 0.1 wt% to 20 wt% or 0.1 wt% to 10 wt% based on the total weight of the silicon-based composite particles (100 wt%). Specifically, the Mg element or Li element may be contained in an amount of 0.5 wt% to 8 wt%, or 0.8 wt% to 4 wt%.

[0036] In one embodiment of the present specification, the Mg element or Li element may be included in an amount of 0.1 wt% to 20 wt%, or 0.1 wt% to 10 wt%, based on the total weight of the negative electrode active material being 100%. Specifically, the Mg element or Li element may be included in an amount of 0.5 wt% to 8 wt%, or 0.8 wt% to 4 wt%. When the above range is satisfied, the Mg compound and Li compound are included in the negative electrode active material in appropriate amounts, so that the volume change of the negative electrode active material during charging and discharging of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0037] The content of the Mg element or Li element can be confirmed by ICP analysis. For the ICP analysis, a certain amount (about 0.01 g) of the negative electrode active material is accurately taken and then transferred to a platinum crucible, and nitric acid, hydrofluoric acid, and sulfuric acid are added to completely decompose it on a hot plate. Then, using an inductively coupled plasma optical emission spectrometer (ICPAES, Perkin-Elmer 7300), the intensity of a standard solution prepared using a standard solution (5 mg / kg) is measured at the characteristic wavelength of the Mg element or Li element to create a reference calibration curve. Then, the pretreated sample solution and a blank sample are introduced into the instrument, and the respective intensities are measured to calculate the actual intensities, and the concentrations of each component are calculated by comparing them with the created calibration curve, and the total sum is converted to a theoretical value, so that the contents of the Mg element and Li element in the negative electrode active material produced can be analyzed.

[0038] The BET specific surface area of ​​the silicon-based composite particles is 5m 2 / g~60m 2 / g. Specifically, 10m 2 / g~60m 2 / g, 20m 2 / g~60m 2 / g, 25m 2 / g~60m 2 / g, or 30m 2 / g~60m 2 When the BET specific surface area of ​​the silicon-based composite particles does not satisfy the above range, the discharge capacity and initial efficiency are low, and the normalized capacity decreases with the progress of cycles, resulting in poor cycle characteristics. Specifically, when the BET specific surface area of ​​the silicon-based composite particles is less than 5 m 2 If the ratio is less than 60m / g, swelling increases with the progress of cycling, resulting in poor cycle characteristics. 2 If the carbon nanotube has a molecular weight of 100 / g or more, the coating uniformity is likely to decrease during carbon coating, and the carbon nanotube is likely to be oxidized when exposed to the outside (moisture), resulting in poor capacity and efficiency characteristics.

[0039] The lower limit of the BET specific surface area of ​​the silicon-based composite particles is 5 m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, or 40m 2 / g, with an upper limit of 60m 2 / g, 55m 2 / g, or 50m 2 / g.

[0040] In one embodiment of the present specification, a carbon layer may be provided on the silicon-based composite particles. In this case, the carbon layer may be provided on at least a part of the surface of the silicon-based particles. That is, the carbon layer may be provided partially on the particle surface or on the entire particle surface. In addition, when the silicon-based composite particles include pores, the carbon layer may be provided in the pores. This provides electrical conductivity to the silicon-based composite particles, effectively suppresses volumetric changes in the negative electrode active material including the silicon-based composite particles, and improves the life characteristics of the battery.

[0041] In one embodiment of the present specification, the carbon layer may include at least one of amorphous carbon and crystalline carbon.

[0042] The crystalline carbon may further improve the electrical conductivity of the silicon-based composite particles. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.

[0043] The amorphous carbon can appropriately maintain the strength of the carbon layer and suppress the expansion of the silicon-based composite particles. The amorphous carbon may be a carbon-based material formed by using at least one carbide selected from the group consisting of tar, pitch, and other organic substances, or a hydrocarbon as a source of a chemical vapor deposition process.

[0044] The other carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose, or ketohexose, and combinations thereof.

[0045] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, or hexane, etc. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, or phenanthrene, etc.

[0046] In one embodiment of the present specification, the carbon layer may be included in an amount of 1 wt% to 50 wt% based on the total weight of the negative electrode active material (100 wt%). Specifically, the carbon layer may be included in an amount of 2 wt% to 45 wt%, 3 wt% to 40 wt%, 3 wt% to 30 wt%, 3 wt% to 20 wt%, or 3 wt% to 17 wt%. When the range is satisfied, the conductivity of the negative electrode active material is improved, and the volume change of the negative electrode active material during charging and discharging of the battery is easily suppressed, thereby improving the life characteristics of the battery.

[0047] In one embodiment of the present specification, the thickness of the carbon layer may be 1 nm to 500 nm, specifically, 5 nm to 300 nm. When the thickness satisfies the above range, the volume change of the negative electrode active material is easily suppressed, and the side reaction between the electrolyte and the negative electrode active material is suppressed, thereby improving the life characteristics of the battery.

[0048] In one embodiment of the present specification, the BET specific surface area of ​​the negative electrode active material is 2 m2 / g~15m 2 / g. Specifically, 2m 2 / g~13m 2 / g, 2m 2 / g~12m 2 / g, or 2.5m 2 / g~12m 2 When the above range is satisfied, the side reaction between the electrolyte and the negative active material during charging and discharging of the battery can be reduced, and the life characteristics of the battery can be improved. 2 If it is less than 15m / g, swelling increases with the progress of cycles, resulting in poor cycle characteristics. 2 If it exceeds 1 / g, there is a problem that side reactions with the electrolyte increase, the rheological properties of the slurry become poor, and the life characteristics of the battery are reduced.

[0049] The lower limit of the BET specific surface area of ​​the negative electrode active material is 2 m 2 / g, 2.5m 2 / g, 3m 2 / g, 4m 2 / g, 6m 2 / g, 8m 2 / g, or 10m 2 / g, with an upper limit of 15m 2 / g, 13m 2 / g, or 12m 2 / g.

[0050] The BET specific surface area of ​​the negative active material is generally lower than that of metal-doped silicon-based particles containing a carbon layer. In the case of conventional particles, it is difficult to control the BET specific surface area of ​​the silicon-based particles, and the BET specific surface area of ​​the negative active material is large, resulting in poor coating uniformity during carbon coating. However, in the present invention, the BET specific surface area of ​​the silicon-based composite particles is set to 60 m 2 / g, the BET specific surface area of ​​the negative active material can be efficiently controlled, and the carbon layer can be uniformly coated to more easily ensure powder conductivity.

[0051] In this specification, powder density means the weight per unit volume of the substance to be measured that has been made into a pellet, and means the apparent density of the substance to be measured.

[0052] In this specification, powder conductivity refers to the surface resistance value measured after forming a powder of a substance to be measured into a pellet and converting it into conductivity.

[0053] In this specification, powder conductivity can be measured using an HPRM-1000 device manufactured by HAN TECH. Specifically, an empty holder (diameter 10 mm) is placed on 4-probe, and the initial thickness is measured when the initial pressure is 10 kgf. After checking the initial thickness of the holder, about 3 g of active material is placed in the holder (diameter 10 mm), the holder is placed on 4-probe, and sample information is input. Pressure is applied to the holder containing the sample, and the powder conductivity can be measured based on the powder density at that pressure.

[0054] The powder conductivity of the negative electrode active material may be 0.05 S / cm to 1 S / cm at a powder density of 1.4 g / cc. Specifically, it may be 0.05 S / cm to 0.9 S / cm, or 0.1 S / cm to 0.8 S / cm. The lower limit of the powder conductivity may be 0.05 S / cm, 0.08 S / cm, 0.1 S / cm, 0.2 S / cm, 0.3 S / cm, 0.4 S / cm, or 0.5 S / cm, and the upper limit may be 1 S / cm, 0.9 S / cm, or 0.8 S / cm.

[0055] In the case of conventional general particles, the BET specific surface area of ​​the silicon-based composite particles is large, and the powder conductivity is less than 0.05 S / cm, so that the normalized capacity decreases with the progress of cycles, resulting in poor cycle characteristics. Specifically, since the silicon-based composite particles have almost no conductivity, when the powder conductivity of the negative electrode active material is less than 0.05 S / cm, the charge / discharge is not easy, so the capacity and efficiency decrease, and the cycle characteristics may be poor. On the other hand, when the powder conductivity exceeds 1 S / cm, when the negative electrode active material is mixed with a carbon-based negative electrode active material (e.g., graphite) and used as a negative electrode, Li present in the carbon-based negative electrode active material is easily diffused into the silicon-based composite particles during high-temperature storage, resulting in a problem of a decrease in capacity due to the loss of Li ions.

[0056] In contrast, the negative electrode active material according to the present invention can exhibit a powder conductivity of 0.05 S / cm to 1 S / cm by the heat treatment step and the carbon layer formation step described below. By having the above powder conductivity, the conductivity of the negative electrode active material can be sufficiently ensured, and a decrease in capacity due to loss of Li ions during use in a negative electrode can be prevented.

[0057] Therefore, the negative electrode active material of the present invention includes silicon-based composite particles having a low level of BET specific surface area, and since the negative electrode active material has a low level of BET specific surface area and high powder conductivity, it is possible to reduce side reactions with the electrolyte and to uniformly and effectively arrange the carbon coating layer, thereby improving the initial efficiency and life characteristics of the battery.

[0058] In contrast, even if the BET specific surface area and powder conductivity of the negative electrode active material satisfy the above ranges, if the BET specific surface area of ​​the silicon-based composite particles does not satisfy the above ranges, there is a problem that when the silicon-based composite particles are exposed to the outside (moisture), the capacity and efficiency decrease due to an oxidation reaction.

[0059] In addition, even if the powder conductivity of the negative electrode active material and the BET specific surface area of ​​the silicon-based composite particles satisfy the above ranges, if the BET specific surface area of ​​the negative electrode active material does not satisfy the above ranges, there is a problem in that a side reaction with the electrolyte during charging / discharging is significant, and capacity reduction due to cycling is significant.

[0060] In addition, even if the BET specific surface area of ​​the silicon-based composite particles and the BET specific surface area of ​​the negative electrode active material satisfy the above ranges, if the powder conductivity of the negative electrode active material does not satisfy the above ranges, there are problems in that charge / discharge does not proceed due to low conductivity, and in the case of a graphite mixed composition, Li present in the graphite during high-temperature storage is easily diffused into the silicon-based composite particles, resulting in a decrease in capacity due to loss of Li ions.

[0061] Therefore, the negative electrode active material of the present invention, in which the BET specific surface area of ​​the silicon-based composite particles, the BET specific surface area of ​​the negative electrode active material and the powder conductivity all satisfy the above-mentioned ranges, is effective in improving the initial efficiency and life characteristics of the battery.

[0062] In one embodiment of the present specification, the silicon-based composite particles may further include pores.

[0063] In the present specification, the size of the pores contained in the silicon-based composite particles means the size excluding the carbon layer provided in the pores.

[0064] In one embodiment of the present specification, the size of the pores may be 50 nm or less, specifically, may be 2 nm to 45 nm, and more specifically, may be 2 nm to 40 nm.

[0065] In another embodiment, the size of the pores may be from 5 nm to 40 nm, or from 10 nm to 40 nm, or from 20 nm to 40 nm.

[0066] In yet another embodiment, the size of the pores may be from 2 nm to 30 nm, or from 4 nm to 25 nm, or from 5 nm to 20 nm.

[0067] In one embodiment of the present specification, the lower limit of the pore size may be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 10 nm, 15 nm, or 20 nm, and the upper limit may be 50 nm, 45 nm, 40 nm, 35 nm, 30 nm, 25 nm, or 20 nm.

[0068] When the pore size exceeds 50 nm, the side reaction between the electrolyte and the silicon-based composite particles increases, and the battery life characteristics deteriorate. The pore size is specially controlled by processes such as synthesis, etching, and additional heat treatment of the silicon-based composite particles, and corresponds to a lower value than the pore size of conventional silicon-based composite particles.

[0069] As described above, the silicon-based composite particles further include pores, which can eliminate the irreversible phase of the silicon-based composite particles to increase the initial efficiency of the battery, can accommodate the volume change of the silicon-based composite particles, and can easily ensure powder conductivity by disposing a carbon layer inside the pores. Also, by controlling the size of the pores as described above, side reactions with the electrolyte during charging and discharging of the battery can be reduced, thereby improving the life characteristics of the battery.

[0070] When the silicon-based composite particles further contain pores as described above, the BET specific surface area of ​​the negative electrode active material is 10 m 2 / g~15m 2 It is preferable that the molecular weight is 1 / g.

[0071] The average particle size (D 50 ) may be 2 μm to 15 μm, specifically 3 μm to 12 μm, and more specifically 4 μm to 10 μm. When the above range is satisfied, a side reaction between the negative electrode active material and the electrolyte is controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved.

[0072] <Method of manufacturing negative electrode active material> The negative electrode active material according to the above-mentioned embodiment is SiO xThe step of manufacturing silicon-based composite particles containing (0 < x < 2) and a Mg compound or a Li compound; and it can be manufactured by a method including the step of providing a carbon layer on the surface of the silicon-based composite particles.

[0073] In one embodiment of the present specification, the SiO x The silicon-based composite particles containing (0 < x < 2) and a Mg compound or a Li compound may be formed by the steps of vaporizing a powder obtained by mixing Si powder and SiO2 powder and a Mg precursor or a Li precursor respectively and then mixing them to form a mixed gas; and heat-treating the mixed gas at 500°C to 1000°C.

[0074] In one embodiment of the present specification, the method for manufacturing the negative electrode active material may further include the step of cooling the silicon-based composite particles to room temperature at a rate of 2°C / min to 60°C / min after the step of manufacturing the silicon-based composite particles.

[0075] In one embodiment of the present specification, the silicon-based composite particles containing the Mg compound may be formed by the steps of vaporizing a powder obtained by mixing Si powder and SiO2 powder and a Mg precursor respectively and then mixing them to form a mixed gas; and heat-treating the mixed gas at 500°C to 1000°C.

[0076] The mixed powder of the Si powder and the SiO2 powder may be heat-treated and vaporized at 1000°C to 1800°C or 1200°C to 1500°C.

[0077] The Mg precursor may be Mg powder, and it may be heat-treated and vaporized at 500°C to 1200°C or 600°C to 800°C. By making the materials react in a gaseous state in this way, Mg can be uniformly distributed within the silicon-based oxide particles.

[0078] The heat treatment may be carried out at 500° C. to 1000° C., 600° C. to 900° C., 650° C. to 850° C., or 700° C. to 800° C. for 1 hour to 4 hours or 2 hours to 3 hours, and may be carried out in a vacuum state.

[0079] In the silicon-based oxide particles, the Mg compound may include the above-mentioned Mg silicate, Mg silicide, Mg oxide, etc.

[0080] In one embodiment of the present invention, after the step of producing the silicon-based composite particles, the silicon-based composite particles may be cooled to room temperature at a rate of 2° C. / min to 60° C. / min.

[0081] The temperature decreasing step may be carried out at a rate of 2° C. / min to 60° C. / min, 5° C. / min to 50° C. / min, or 5° C. / min to 10° C. / min.

[0082] By the above-mentioned heat treatment and cooling steps, the BET specific surface area of ​​the silicon-based composite particles can be easily controlled.

[0083] The particle size of the Mg-containing silicon-based composite particles produced by the above-mentioned method may be adjusted, if necessary, by a pulverization method such as mechanical milling.

[0084] In the above-mentioned production method, a Li precursor may be used instead of the Mg precursor to produce silicon-based composite particles containing a Li compound.

[0085] In one embodiment of the present specification, the silicon-based composite particles containing the Li compound may be formed by the steps of: vaporizing a mixture of Si powder and SiO2 powder and a Li precursor, and then mixing them to form a mixed gas; and heat-treating the mixed gas at 500°C to 1000°C in a vacuum state.

[0086] The mixed powder of the Si powder and the SiO2 powder may be heat-treated at 1000°C to 1800°C or 1200°C to 1500°C to be vaporized.

[0087] The Li precursor may be Li powder, which may be vaporized by heat treatment at 500° C. to 1200° C. or 700° C. to 900° C. In this way, the material reacts in a gaseous state, whereby Li can be uniformly distributed within the silicon-based oxide particles.

[0088] The heat treatment may be carried out at 500° C. to 1000° C., 600° C. to 900° C., 650° C. to 800° C., or 650° C. to 750° C. for 1 to 4 hours or 2 to 3 hours, and may be carried out in a vacuum state.

[0089] In the silicon-based composite particles, the Li compound may include the above-mentioned Li silicate, Li silicide, Li oxide, and the like.

[0090] In one embodiment of the present invention, after the step of producing the silicon-based composite particles, the silicon-based composite particles may be cooled to room temperature at a rate of 2° C. / min to 60° C. / min.

[0091] The temperature decreasing step may be carried out at a rate of 2° C. / min to 60° C. / min, 5° C. / min to 50° C. / min, or 5° C. / min to 10° C. / min.

[0092] By the above-mentioned heat treatment and cooling steps, the BET specific surface area of ​​the silicon-based composite particles can be easily controlled.

[0093] In one embodiment of the present specification, a step of etching the silicon-based composite particles may be included after the step of producing the silicon-based composite particles.

[0094] In this case, etching may be performed using an acid or a base, and the acid may be at least one of hydrofluoric acid (HF), nitric acid (HNO3), sulfuric acid (H2SO4), and hydrochloric acid (HCl), and the base may be at least one of sodium hydroxide (NaOH) and potassium hydroxide (KOH). Specifically, a mixed solution of hydrofluoric acid and ethanol may be used during the etching. The Mg compound phase, Li compound, or SiO2 of the silicon-based composite particles is removed by the etching step, thereby improving the discharge capacity and efficiency of the battery. The etching may be performed for 10 minutes to 3 hours, specifically, for 30 minutes to 2 hours.

[0095] The etching step can allow the silicon-based composite particles to further include pores.

[0096] The BET specific surface area of ​​the silicon-based composite particles prepared as above is 5m 2 / g~60m 2 / g. Specifically, 10m 2 / g~60m 2 / g, 20m 2 / g~60m 2 / g, or 30m 2 / g~60m 2 / g.

[0097] In the step of providing the carbon layer, the carbon layer may be manufactured by using a chemical vapor deposition (CVD) method using a hydrocarbon gas, or by carbonizing a material serving as a carbon source.

[0098] For example, the step of providing a carbon layer may be performed by injecting a carbonaceous raw material gas (hydrocarbon gas) such as methane gas and performing heat treatment in a rotary tubular furnace. Specifically, the silicon-based composite particles are placed in a rotary tubular furnace, the temperature is raised to 600°C to 1200°C, 800°C to 1150°C, 900°C to 1050°C, or 950°C to 1,000°C at a rate of 3 to 10°C / min or about 5°C / min, and argon gas and a carbonaceous material raw material gas are introduced while rotating the rotary tubular furnace, and heat treatment is performed for 30 minutes to 8 hours to form a carbon layer.

[0099] <Negative electrode> A negative electrode according to an embodiment of the present specification may include the negative electrode active material described above. Specifically, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material. Furthermore, the negative electrode active material layer may further include a binder and / or a conductive material.

[0100] The negative electrode active material layer may be formed by applying a negative electrode slurry containing a negative electrode active material, a binder, a thickener, and / or a conductive material to at least one surface of a current collector, followed by drying and rolling.

[0101] The negative electrode slurry may further include an additional negative electrode active material.

[0102] The additional negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the additional negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, lithium titanium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, either low-crystalline carbon or high-crystalline carbon may be used as the carbon material. Typical low-crystalline carbons are soft carbon and hard carbon, and typical high-crystalline carbons are amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbons such as petroleum or coal tar pitch derived cokes.

[0103] The additional anode active material may be a carbon-based anode active material.

[0104] The carbon-based negative electrode active material may be graphite, specifically, artificial graphite or natural graphite.

[0105] In an embodiment of the present invention, the weight ratio of the negative electrode active material and the additional negative electrode active material contained in the negative electrode slurry may be 1:99 to 90:10, specifically, 5:95 to 60:40, or 10:90 to 50:50.

[0106] The content of the negative electrode active material according to the present invention may be 1 to 50 parts by weight based on the total negative electrode active material, specifically, 5 to 30 parts by weight, 8 to 20 parts by weight, or 10 to 15 parts by weight.

[0107] The negative electrode slurry may include a solvent for forming a negative electrode slurry. Specifically, the solvent for forming a negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, specifically, distilled water, in order to facilitate dispersion of components.

[0108] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector. The thickness of the current collector may be 6 μm to 20 μm, but the thickness of the current collector is not limited thereto.

[0109] The binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.

[0110] The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0111] <Secondary battery> A secondary battery according to an embodiment of the present specification may include the negative electrode according to the above-mentioned embodiment. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.

[0112] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0113] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0114] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li-metal.

[0115] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.

[0116] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause chemical changes in the battery that is constructed and has electronic conductivity.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one of these may be used alone or a mixture of two or more of them may be used.

[0117] In addition, the positive electrode binder plays a role of improving adhesion between positive electrode active material particles and adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.

[0118] The separator is a separator that separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is normally used as a separator in a secondary battery can be used without any particular restrictions, and it is particularly preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.

[0119] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0120] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0121] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0122] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, can be preferably used because they are high-viscosity organic solvents with high dielectric constants that easily dissociate lithium salts, and can be further preferably used by mixing such cyclic carbonates with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, so that an electrolyte having high electrical conductivity can be prepared.

[0123] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte solution. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2- , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.

[0124] In addition to the constituents of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0125] One embodiment of the present specification provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore can be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system.

[0126] Hereinafter, the present specification will be described in detail with reference to examples in order to specifically explain the present specification. However, the examples according to the present specification may be modified in various different forms, and the scope of the present application should not be interpreted as being limited to the examples described below. The examples of the present application are provided to more completely explain the present specification to those having average knowledge in the art.

[0127] <Examples and Comparative Examples> Example 1: Preparation of negative electrode active material (1) Manufacturing of silicon-based composite particles A homogeneous mixture of Si powder and SiO2 powder in a molar ratio of 1:1 and Mg were heat-treated at 1400°C and 700°C, respectively, in a reduced pressure atmosphere to vaporize the Si powder, SiO2 powder, and Mg. The vaporized mixed gas of the Si powder, SiO2 powder, and Mg was heat-treated in a vacuum chamber at 800°C for 3 hours, and then cooled at a rate of 5°C / min to produce particles. The particles were pulverized in a jet mill to produce an average particle size (D 50 ) is 5 μm, and the BET specific surface area is 29 m 2 The silicon-based composite particles were formed with a molecular weight of 1 / g.

[0128] (2) Manufacturing of negative electrode active material Thereafter, while maintaining an inert atmosphere by flowing Ar gas, the silicon-based composite particles were placed in the hot zone of a CVD apparatus, and the methane was blown into the hot zone at 900° C. using Ar as a carrier gas for 3 hours and 10 minutes. -1 The silicon-based composite particles were reacted at 1000 MPa (torr) (carbon coating) to prepare a negative active material having a carbon layer formed on the surface of the silicon-based composite particles.

[0129] The BET specific surface area of ​​the negative electrode active material particles is 8.2 m 2 / g, and the powder conductivity at a powder density of 1.4 g / cc was 0.1 S / cm.

[0130] The C content and Mg content of the negative electrode active material particles were 3.5 wt.% and 6.0 wt.%, respectively.

[0131] Example 2: Preparation of negative electrode active material A negative electrode active material was prepared in the same manner as in Example 1, except that in preparing the silicon-based composite particles, the mixed gas was heat-treated at 800°C for 2 hours with a temperature reduction rate of 50°C / min, and in preparing the negative electrode active material particles, the carbon coating time was 7 hours.

[0132] Example 3: Preparation of negative electrode active material (1) Manufacturing of silicon-based composite particles A homogeneous mixture of Si powder and SiO2 powder in a molar ratio of 1:1 and Mg were heat-treated at 1400°C and 700°C, respectively, in a reduced pressure atmosphere to vaporize the Si powder, SiO2 powder, and Mg. The vaporized mixed gas of the Si powder, SiO2 powder, and Mg was heat-treated in a vacuum chamber at 800°C for 2 hours, and then cooled at a rate of 50°C / min to produce particles. The particles were pulverized in a jet mill to produce an average particle size (D 50 ) formed 5 μm preliminary silicon-based composite particles.

[0133] Then, a mixed solution of hydrofluoric acid and ethanol was used as an etching solution, and the silicon-based composite particles were added to the etching solution in a weight ratio of 20:1. After mixing for about 30 minutes, the silicon-based composite particles were filtered, washed, and dried to obtain a silicon-based composite having a BET specific surface area of ​​59 m. 2 / g of silicon-based composite particles were formed.

[0134] (2) Manufacturing of negative electrode active material Thereafter, while maintaining an inert atmosphere by flowing Ar gas, the silicon-based composite particles were placed in the hot zone of a CVD apparatus, and the methane was blown into the hot zone at 900° C. using Ar as a carrier gas for 8 hours and 10 minutes. -1 The reaction was carried out at a pressure of 1000 MPa (torr) to prepare a negative electrode active material having a carbon layer formed on the surface of the silicon-based composite particles.

[0135] The average size of the pores contained in the negative electrode active material was 39 nm.

[0136] The BET specific surface area of ​​the negative electrode active material particles is 11.9 m 2 / g and the powder conductivity was 0.8 S / cm.

[0137] The C content and Mg content of the negative electrode active material particles were 16.2 wt. % and 2.9 wt. %, respectively.

[0138] Example 4: Preparation of negative electrode active material A negative active material was prepared in the same manner as in Example 1, except that the cooling rate after heat treatment in the preparation of silicon-based composite particles was 10° C. / min, and the carbon coating time in the preparation of negative active material particles was 4 hours.

[0139] Example 5: Preparation of negative electrode active material (1) Manufacturing of silicon-based composite particles A homogeneous mixture of Si powder and SiO2 powder in a 1:1 molar ratio was heat-treated with Li in a reduced pressure atmosphere at 1400°C and 800°C, respectively, to vaporize the Si powder, SiO2 powder, and Li. The vaporized mixture of Si powder, SiO2 powder, and Li was heat-treated in a vacuum chamber at 700°C for 3 hours, and then cooled at a rate of 5°C / min to produce particles. The particles were pulverized in a jet mill to produce an average particle size (D 50 ) is 5 μm, and the BET specific surface area is 21 m 2 Preliminary silicon-based composite particles having a particle size of 1 / g were formed.

[0140] (2) Manufacturing of negative electrode active material Thereafter, while maintaining an inert atmosphere by flowing Ar gas, the silicon-based composite particles were placed in the hot zone of a CVD apparatus, and the methane was blown into the hot zone at 900° C. using Ar as a carrier gas for 3 hours and 10 minutes. -1 The reaction was carried out at a pressure of 1000 MPa (torr) to prepare a negative electrode active material having a carbon layer formed on the surface of the silicon-based composite particles.

[0141] The BET specific surface area of ​​the negative electrode active material particles is 2.6 m 2 / g and the powder conductivity was 0.3 S / cm.

[0142] The C content and Li content of the negative electrode active material particles were 4.5 wt.% and 5.9 wt.%, respectively.

[0143] Example 6: Preparation of negative electrode active material A negative active material was prepared in the same manner as in Example 5, except that the Li content of the negative active material particles was increased to 9.1 wt. %.

[0144] Comparative Example 1: Production of negative electrode active material A negative active material was prepared in the same manner as in Example 1, except that the heat treatment of the mixed gas during the preparation of the silicon-based composite particles was performed at 1100° C. for 3 hours.

[0145] Comparative Example 2: Production of negative electrode active material A negative active material was prepared in the same manner as in Example 1, except that the mixed gas was not heat-treated during the preparation of silicon-based composite particles, and the temperature reduction rate was set to 70° C. / min, and the carbon coating time during the preparation of negative active material particles was set to 8 hours and 30 minutes.

[0146] Comparative Example 3: Production of negative electrode active material A negative active material was prepared in the same manner as in Example 1, except that the heat treatment of the mixed gas during the preparation of the silicon-based composite particles was performed at 1100° C. for 4 hours, and the carbon coating time during the preparation of the negative active material particles was set to 3 hours and 30 minutes.

[0147] Comparative Example 4: Production of negative electrode active material A negative electrode active material was prepared in the same manner as in Example 3, except that no heat treatment was performed during the preparation of silicon-based composite particles, the temperature reduction rate was set to 75° C. / min, the etching time was set to 1 hour, and the carbon coating time during the preparation of negative electrode active material particles was set to 2 hours.

[0148] Comparative Example 5: Production of negative electrode active material A negative active material was prepared in the same manner as in Example 1, except that the heat treatment in the preparation of the silicon-based composite particles was performed at 1100° C. for 4 hours, and the carbon coating time in the preparation of the negative active material particles was set to 2 hours.

[0149] Comparative Example 6: Production of negative electrode active material A negative electrode active material was prepared in the same manner as in Example 3, except that no heat treatment was performed during the preparation of silicon-based composite particles, the temperature reduction rate was set to 70° C. / min, the etching time was set to 1 hour, and the carbon coating time during the preparation of negative electrode active material particles was set to 8 hours and 30 minutes.

[0150] Comparative Example 7: Production of negative electrode active material A negative active material was prepared in the same manner as in Example 5, except that the heat treatment in the preparation of the silicon-based composite particles was performed at 1100° C. for 3 hours, and the carbon coating time in the preparation of the negative active material particles was 3 hours and 30 minutes.

[0151] Comparative Example 8: Production of negative electrode active material A negative electrode active material was prepared in the same manner as in Example 5, except that no heat treatment was performed during the preparation of silicon-based composite particles, the temperature reduction rate was set to 70° C. / min, and the carbon coating time during the preparation of negative electrode active material particles was set to 8 hours and 30 minutes.

[0152] Comparative Example 9: Production of negative electrode active material A negative active material was prepared in the same manner as in Example 1, except that the carbon coating source was changed to pitch and the coating time was set to 4 hours.

[0153] The negative active materials prepared in the above examples and comparative examples are as shown in Table 1 below.

[0154] [Table 1]

[0155] The specific surface areas of the silicon-based composite particles and the negative electrode active material were measured by the BET (Brunauer-Emmett-Teller; BET) method. Specifically, the specific surface areas were measured by the BET 6-point method using a porosimetry analyzer (Belsorp-II mini, Bell Japan Inc.) by nitrogen gas adsorption and flow method.

[0156] The pore size was measured by a formula according to the BJH (Barrett-Joyner-Halenda) method using nitrogen adsorption. Specifically, the pore area according to the pore size was calculated using a BELSORP-mini II model manufactured by BEL Japan, and then the pore size (Dp / nm) showing the largest pore area (dVp / dDp) was measured.

[0157] The contents of Mg and Li elements were measured by ICP analysis. Specifically, a certain amount (about 0.01 g) of the negative electrode active material was taken and transferred to a platinum crucible, and nitric acid, hydrofluoric acid, and sulfuric acid were added to completely decompose it on a hot plate. Then, using an inductively coupled plasma optical emission spectrometer (ICPAES, Perkin-Elmer 7300), the intensity of a standard solution prepared using a standard solution (5 mg / kg) was measured at the characteristic wavelength of each element to create a reference calibration curve. Then, the pretreated sample solution and a blank sample were introduced into the instrument, and the intensity of each was measured to calculate the actual intensity. The concentration of each component was calculated by comparing it with the created calibration curve, and the total sum was converted to a theoretical value, and the Mg and Li element contents of the negative electrode active material prepared were analyzed.

[0158] The average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 ) was measured on a Malvern instrument using the laser diffraction method.

[0159] Powder conductivity was measured using a HAN TECH HPRM-1000 instrument. An empty holder (10 mm diameter) was placed on the 4-probe, and the initial thickness was measured when the initial pressure was 10 kgf. After checking the initial thickness of the holder, approximately 3 g of active material was placed in the holder (10 mm diameter), the holder was placed on the 4-probe, and the sample information was entered. Pressure was then applied to the holder containing the sample, and the powder conductivity was measured at a powder density of 1.4 g / cc.

[0160] <Experimental example: discharge capacity and initial efficiency> The negative active material prepared in Example 1 was mixed with carbon black as a conductive material and lithium polyacrylic acid (Li-PAA) as a binder in a weight ratio of 80:10:10 with water (H2O) as a solvent to prepare a homogeneous negative electrode slurry. The prepared negative electrode slurry was coated on one side of a copper current collector, dried, rolled, and punched to a certain size to prepare a negative electrode.

[0161] A Li metal was used as a counter electrode, and a polyolefin separator was placed between the negative electrode and the Li metal. An electrolyte in which 1M LiPF6 was dissolved in a solvent made of ethylene carbonate (EC) and diethyl carbonate (EMC) mixed in a volume ratio of 30:70 was then injected to prepare a coin-type half cell of Example 1A.

[0162] Coin-type half cells of Examples 2A to 6A and Comparative Examples 1A to 9A were manufactured in the same manner as in Example 1A, except that the silicon-based composites of Examples 2 to 6 and Comparative Examples 1 to 9 were used. Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cut-off) Discharge condition: CC (constant current) condition 1.5V voltage cut-off

[0163] From the results of one charge and discharge, the discharge capacity (mAh / g) and initial efficiency (%) were calculated and are shown in Table 2 below.

[0164] <Experimental example: Evaluation of life (capacity retention) characteristics> The negative electrode active materials of Examples 1 to 6 and Comparative Examples 1 to 9 and natural graphite were mixed in a weight ratio of 1:9 to prepare a mixed negative electrode active material, carbon black as a conductive material, and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) as binders in a weight ratio of mixed negative electrode active material:conductive material:binder (CMC):binder (styrene butadiene) = 95.4:1:1.1:2.5, together with water as a solvent, to prepare a negative electrode slurry (solid content was about 49 wt% based on the total weight of the negative electrode slurry). The negative electrode slurry was applied to a copper (Cu) metal thin film as a negative electrode current collector, dried, and punched to a certain size to prepare a negative electrode.

[0165] Li metal was used as the counter electrode. A polyolefin separator was placed between the negative electrode and Li metal, and an electrolyte of 1M LiPF6 dissolved in a solvent of ethylene carbonate (EC) and diethyl carbonate (EMC) mixed in a volume ratio of 3:7 was injected to fabricate a lithium coin-type half cell.

[0166] The produced batteries were charged and discharged to evaluate their capacity retention rates, which are shown in Table 2 below.

[0167] The first and second cycles were charged and discharged at 0.1C, and the third to 50th cycles were charged and discharged at 0.5C. -Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cut-off) -Discharge condition: CC (constant current) condition 1.5V voltage cut-off The capacity retention rate was calculated as follows. -Capacity retention rate (%) = (50 discharge capacity / 1 discharge capacity) x 100

[0168] [Table 2]

[0169] In the above-mentioned Examples 1 to 6, the silicon-based composite particles contain an Mg compound or a Li compound, and the silicon-based composite particles are 5 μm or less. 2 / g~60m 2 / g, and the negative electrode active material after the carbon layer is formed has a BET specific surface area of ​​2m 2 / g~15m 2 The silicon-based composite particles have an appropriately low BET specific surface area and are appropriately provided with a carbon layer to exhibit appropriate powder conductivity, thereby making it possible to improve the initial efficiency and life characteristics of the battery.

[0170] In contrast, in the case of Comparative Examples 1, 3, 5, and 7, the heat treatment temperature was high, and the BET specific surface area of ​​the silicon-based composite particles was excessively low, so that the swelling characteristics due to charge / discharge could not be effectively suppressed, and therefore, it was confirmed that the discharge capacity, initial efficiency, and capacity retention rate were reduced.

[0171] It was confirmed that when the BET specific surface area of ​​the silicon-based composite particles is excessively high, as in Comparative Examples 2, 4, 6, and 8, the coating uniformity decreases during carbon coating, and the particles are easily oxidized when exposed to the outside (moisture), resulting in particularly poor capacity and efficiency characteristics.

[0172] Even if the BET specific surface area of ​​the silicon-based composite particles and the negative active material is satisfied as in Comparative Example 9, if the powder conductivity of the negative active material is excessively low, it is difficult to charge / discharge the battery, resulting in reduced capacity and efficiency, and poor cycle characteristics.

Claims

1. SiO x (0<x<2) and a Mg compound or a Li compound; and a carbon layer provided on the silicon-based composite particle, The silicon-based composite particles have a BET specific surface area of ​​5 m 2 / g ~ 60m 2 / g, The BET specific surface area of ​​the negative electrode active material is 2 m 2 / g to 15m 2 / g, A negative electrode active material having a powder conductivity of 0.1 S / cm to 0.8 S / cm at a powder density of 1.4 g / cc.

2. The BET specific surface area of ​​the silicon-based composite particles is 20 m 2 / g ~ 60m 2 The negative electrode active material according to claim 1 , wherein the molecular weight of the negative electrode active material is 1 / g.

3. The BET specific surface area of ​​the negative electrode active material is 2 m 2 / g ~ 12m 2 The negative electrode active material according to claim 1 , wherein the molecular weight of the negative electrode active material is 1 / g.

4. The negative electrode active material according to claim 1 , wherein the silicon-based composite particles further include pores.

5. The negative electrode active material according to claim 4, wherein the pore size is 2 nm to 45 nm.

6. The negative electrode active material of claim 1, wherein the Mg element or the Li element is included in an amount of 0.1 wt % to 20 wt % based on 100 wt % of the total weight of the negative electrode active material.

7. The negative electrode active material according to claim 1 , wherein the Mg compound includes at least one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide.

8. The negative electrode active material according to claim 1 , wherein the Li compound includes at least one selected from the group consisting of Li silicate, Li silicide, and Li oxide.

9. The negative electrode active material of claim 1 , wherein the carbon layer is included in an amount of 1 wt % to 50 wt % based on 100 wt % of the total weight of the negative electrode active material.

10. SiO x (0<x<2) and preparing silicon-based composite particles containing a Mg compound or a Li compound; and Providing a carbon layer on the surface of the silicon-based composite particle. The method for producing the negative electrode active material according to any one of claims 1 to 9, comprising:

11. The method for producing an anode active material according to claim 10, further comprising the step of cooling the silicon-based composite particles to room temperature at a rate of 2° C. / min to 60° C. / min after the step of producing the silicon-based composite particles.

12. A negative electrode comprising the negative electrode active material according to any one of claims 1 to 9.

13. The anode of claim 12 , wherein the anode further comprises a carbon-based anode active material.

14. A secondary battery comprising the negative electrode according to claim 12.

Citation Information

Patent Citations

  • Lithium-containing silicon oxide powder and method for production thereof

    JP2003160328A

  • Nonaqueous electrolyte battery

    JP2008288059A

  • Electrode active material for secondary battery

    JP2014026949A

  • Negative electrode active material for lithium secondary battery and its manufacturing method

    JP2018523898A

  • Negative electrode material for lithium ion battery, negative electrode for lithium ion battery, and lithium ion battery

    JP2019220350A